2014
DOI: 10.1371/journal.pgen.1004109
|View full text |Cite
|
Sign up to set email alerts
|

DAF-16/FoxO Directly Regulates an Atypical AMP-Activated Protein Kinase Gamma Isoform to Mediate the Effects of Insulin/IGF-1 Signaling on Aging in Caenorhabditis elegans

Abstract: The DAF-16/FoxO transcription factor controls growth, metabolism and aging in Caenorhabditis elegans. The large number of genes that it regulates has been an obstacle to understanding its function. However, recent analysis of transcript and chromatin profiling implies that DAF-16 regulates relatively few genes directly, and that many of these encode other regulatory proteins. We have investigated the regulation by DAF-16 of genes encoding the AMP-activated protein kinase (AMPK), which has α, β and γ subunits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 86 publications
3
39
0
Order By: Relevance
“…We have determined that this is due to loss of Fkh1/2-dependent SNF1 expression. SNF4 expression was not affected despite the analogous Daf16/ FOXO transcription factor in Caenorhabditis elegans contributing to the expression of the ␥ subunit of an atypical AMPKrelated enzyme (60). In yeast, Fkh1 alone binds to the SNF1 promoter, consistent with its greater impact on returning SNF1 expression toward normal as compared with Fkh2 (Fig.…”
Section: Snf1 Transcription Is Influenced By Yeast Forkhead Pro-mentioning
confidence: 74%
“…We have determined that this is due to loss of Fkh1/2-dependent SNF1 expression. SNF4 expression was not affected despite the analogous Daf16/ FOXO transcription factor in Caenorhabditis elegans contributing to the expression of the ␥ subunit of an atypical AMPKrelated enzyme (60). In yeast, Fkh1 alone binds to the SNF1 promoter, consistent with its greater impact on returning SNF1 expression toward normal as compared with Fkh2 (Fig.…”
Section: Snf1 Transcription Is Influenced By Yeast Forkhead Pro-mentioning
confidence: 74%
“…We also showed that hif-1 mutations up-regulate AMPK through an unknown mechanism. Recently, HIF-1 was shown to inhibit DAF-16/FOXO activity (61), and DAF-16 elevates AMPK activity by increasing transcription of the genes that encode AMPK subunits (62). Thus, hif-1 mutations may increase AMPK activity by modulating DAF-16.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, DAF-16 can induce the expression of genes encoded by AMPK, which slows aging in Caenorhabiditis elegans. This suggests that DAF-16 and AMPK form a positive feedback loop (64). In mammals, however, the research about this feedback loop has not detected any changes in the γ substrate of AMPK depending on FOXO protein activation (65).…”
Section: Adenosine Monophosphate-activated Protein Kinase (Ampk)mentioning
confidence: 99%